Integrated approaches to testing and assessment as a tool for the hazard assessment and risk characterization of cosmetic preservatives - Canavez, Andrezza Di Pietro Micali; de Oliveira Prado Corrêa, Gabriela [UNESP]; Isaac, Vera Lucia Borges [UNESP]; Schuck, Desiree Cigaran; Lorencini, Marcio (Wiley, 2021)
The safety assessment of cosmetic products is based on the safety of the ingredients, which requires information on chemical structures, toxicological profiles, and exposure data. Approximately 6% of the population is sensitized to cosmetic ingredients, especially preservatives and fragrances. In this context, the aim of this study was to perform a hazard assessment and risk characterization of benzalkonium chloride (BAC), benzyl alcohol (BA), caprylyl glycol (CG), ethylhexylglycerin (EG), chlorphenesin (CP), dehydroacetic acid (DHA), sodium dehydroacetate (SDH), iodopropynyl butylcarbamate (IPBC), methylchloroisothiazolinone and methylisothiazolinone (MCI/MIT), methylisothiazolinone (MIT), phenoxyethanol (PE), potassium sorbate (PS), and sodium benzoate (SB). Considering the integrated approaches to testing and assessment (IATA) and weight of evidence (WoE) as a decision tree, based on published safety reports. The hazard assessment was composed of a toxicological matrix correlating the toxicity level, defined as low (L), moderate (M), or high (H) and local or systemic exposure, considering the endpoints of skin sensitization, skin irritation, eye irritation, phototoxicity, acute oral toxicity, carcinogenicity, mutagenicity/genotoxicity, and endocrine activity. In a risk assessment approach, most preservatives had a margin of safety (MoS) above 100, except for DHA, SDH, and EG, considering the worst-case scenario (100% dermal absorption). However, isolated data do not set up a safety assessment. It is necessary to carry out a rational risk characterization considering hazard and exposure assessment to estimate the level of risk of an adverse health outcome, based on the concentration in a product, frequency of use, type of product, route of exposure, body surface location, and target population.
Keywords: cosmetic preservatives; exposure assessment; hazard assessment; risk characterization; safety evaluation